Pendekatan Model Empiris untuk Prediksi Laju Korosi Material pada Kursi Roda Arm Rest - Ahmat Fahrezy, Egi; Renilaili, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Corrosion is one of the main challenges in the maintenance and durability of materials in various applications, including on wheelchair arm rest. Predicting the rate of corrosion is crucial for enhancing the lifespan and reliability of these devices. This research develops an empirical model approach to predict the corrosion rate of arm rest materials. The model is built based on experimental data obtained from corrosion testing under various environmental conditions. The data is analyzed using linear and non-linear regression methods to find the relationship between environmental variables (such as humidity, temperature, and acidity) and the corrosion rate.